Automatic Generation of Station Catchment Areas: A comparison of Euclidean distance transform algorithm and location-allocation methods - Lin, Ting; Palmer, Richard; Xia, Jianhong (Cecilia); McMeekin, David (IEEE, 2014)
A train station catchment area can be generated in two ways: by surveying train users or by modelling methods. The former method is time consuming and labor intensive. In this paper attention was given to develop methods that automatically generate station catchment areas. This study’s aim was to compare two modelling methods: the Euclidean Distance Transform / Voronoi Diagram Generation method and a location and allocation method for automatically generating station catchment areas. A case study of the Perth Metropolitan area, in Western Australia, was used to implement these two methods. The results from these two methods are consistent and the methods demonstrate robustness for understanding the nature of station catchment areas and provide useful insights for public transport planning in Perth.